The World Under Pressure : How China and India are Influencing the Global Economy and Environment - Dahlman, Carl J. 1950- (India Cambridge University Press, 2013)
The book analyzes the impact of the rapid rise of China and India on existing power relationships worldwide. It examines current frictions that could escalate into trade, cold, and conventional wars. Uniquely, this text also considered the risks that these countries pose to global environmental sustainability because of their growing CO2 emissions.
Include References and Index
Keywords: Economic history -- International economic relations